(untitled) (ESMAT Magazine, 2024)
This research addresses the issue of General Repercussion Theme Nº. 1.234, which deals with the responsibility of federal entities for supplying medicines that are not incorporated into the SUS. Through a special commission and negotiations between the entities, an agreement is sought to define the jurisdiction of the Federal Court and to establish compensation between the federal entities in these claims. The expectation of solving the problem through conciliation and mediation is highlighted, in contrast to a traditional judicial decision, with the objective of guaranteeing access to the fundamental right to health in a more efficient and collaborative way, considering the complexities of the Brazilian federative system. The methodology used relied on bibliographical research, utilizing books, scientific journals and case law related to the subject.